2017
DOI: 10.1111/hepr.12981
|View full text |Cite
|
Sign up to set email alerts
|

Study of the sleep quality and psychological state of patients with hepatitis B liver cirrhosis

Abstract: These results indicated that patients with hepatitis B liver cirrhosis have a disturbed sleep, which might be an MHE symptom, further causing considerable anxiety. Thus, the evaluation of sleep quality and psychological state of patients with hepatitis B liver cirrhosis necessitates further investigation to guide positive intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
(72 reference statements)
2
17
0
Order By: Relevance
“…showed a correlation between NCT-A results and PSQI scores in patients with cirrhosis induced by hepatitis B. [ 24 ] Similarly, we found that cirrhotic patients with MHE had worse EncephalApp results, considered as one of the independent predictors for poor sleep quality in these patients. The correlation may be attributed to poor sleep quality of MHE being associated with the specific neuropsychiatric impairments that can be exactly evaluated by EncephalApp.…”
Section: Discussionsupporting
confidence: 55%
“…showed a correlation between NCT-A results and PSQI scores in patients with cirrhosis induced by hepatitis B. [ 24 ] Similarly, we found that cirrhotic patients with MHE had worse EncephalApp results, considered as one of the independent predictors for poor sleep quality in these patients. The correlation may be attributed to poor sleep quality of MHE being associated with the specific neuropsychiatric impairments that can be exactly evaluated by EncephalApp.…”
Section: Discussionsupporting
confidence: 55%
“…A total of 39 studies assessing symptom prevalence were included (see Supplementary Material). 2058 The majority reported data from North America (16) and Europe (14), although Asia (8) and Africa (1) were also covered. Most were cross-sectional studies conducted while patients were outpatients or stable after hospitalization.…”
Section: Symptom Prevalence Of Patients With End-stage Liver Diseasementioning
confidence: 99%
“…The number of participants differs significantly between studies too. Xiao et al's study 14 has the highest number of participants followed by Stewart et al's study. 20 Interestingly, both studies demonstrate a significant association between depression and HE.…”
Section: Resultsmentioning
confidence: 91%
“…Table 1 highlights a marked discrepancy between the results. Some findings show a significant association between anxiety/depressive disorders and HE, 14,15,20,21 others strongly reject this relationship, 17,18 and another study demonstrates a partial association between specific aspects of each illness. 16 Two studies reveal increased BDI scores in HE, but this result is not compared with that from control groups.…”
Section: Resultsmentioning
confidence: 94%